Justice in J. S. Mill: beyond individualism - Lopera Chaves, María Teresa (Estudios de Filosofía, 1992)
The article is a critique of the exposition made by John Rawls of the moral theory of J.S. Mill. The author shows that Mill is not just another utilitarian. Instead, his use of concepts makes him (in some respects) almost a companion of the contractualists. For this reason, the polar opposition between utilitarianism and contractualism is not adequate in this case.